ANALYTICAL STUDY OF EDUCATIONAL ADJUSTMENT OF NORMAL AND DISABLED STUDENTS - Idris, Umra; Gola, Rajkumari (ShodhKosh: Journal of Visual and Performing Arts, 2024)
It has been found in various studies that adjustment of normal and disabled students has a new effect on the group of students. If the adjustment is good in both the students, then the interest in education increases in both types of normal and disabled students and they are able to get good education by making adjustment among themselves. Similarly, in the field of education, there is a good adjustment among the group of normal and disabled students, due to which they get various opportunities to progress in their education. Normal and disabled students are also able to increase their aspirations by adjusting among themselves. And by joining each other’s group, they develop their complete development. Educational adjustment not only helps in the field of education, it also helps normal and disabled students in the field of overall development of the student such as physical development, mental development and emotional development. Similarly, normal and disabled students remain motivated to learn new things.